The Internal Policy of Armenian King Arshak II - Varshamyan, Edgar (History and Culture, 2022)
To summarize, we can state that Arshak II’s domestic policy is one of the most educational chapters in the Armenian history. From the very beginning of his reign, the Armenian king pursued the idea of strengthening of the state, and his every action in domestic politics was aimed at it. Owing to the temporary lull in the region at the start of his reign, Arshak II was able to greatly consolidate his position inside the country (kingdom). First and foremost, the Armenian king began to return the ministers who had left their domains to the court, appoint border guards in all regions of the kingdom, strengthen the army, and effectively finish the battle for the throne. During the second phase of his reign, the Armenian king was able to maintain a consistent battle against the economically powerful ministers and the church. Firstly, Arshak II established the city of Arshakavan, enabling those displeased with the lords and the church to reside there. Dissatisfied with the king, the ministers attacked the city, destroying it and slaughtering the inhabitants. Then a war erupted amongst the king and the lords, but neither side was victorious. Catholicos Nerses reconciled them at the request of Arshak II and the lords. Not long after the events at Arshakavan, however, Arshak II assaulted the lords, thereby nullifying the agreement. The Kamsarakans were among the first to be punished. To restore the country’s internal unity, Arshak II dismissed Nerses from the position of Catholicos and nominated one of his faithful clergymen, Chunak, as the new Catholicos.